2014
DOI: 10.1038/ncomms5763
|View full text |Cite
|
Sign up to set email alerts
|

Screening of DUB activity and specificity by MALDI-TOF mass spectrometry

Abstract: Deubiquitylases (DUBs) are key regulators of the ubiquitin system which cleave ubiquitin moieties from proteins and polyubiquitin chains. Several DUBs have been implicated in various diseases and are attractive drug targets. We have developed a sensitive and fast assay to quantify in vitro DUB enzyme activity using matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry. Unlike other current assays, this method uses unmodified substrates, such as diubiquitin topoisomers. By ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
353
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(366 citation statements)
references
References 64 publications
13
353
0
Order By: Relevance
“…Similar results were found by Ritorto et al (2014) who compared the performance of the Acclaim® 120 C18 and the Acclaim® RSLC C18 PA2 to separate tryptic digested proteins from cell lysate. The researchers found that the Acclaim® RSLC C18 PA2 had higher efficiencies and exhibited higher polarity of selectivity.…”
Section: Hplc Columnsupporting
confidence: 69%
See 1 more Smart Citation
“…Similar results were found by Ritorto et al (2014) who compared the performance of the Acclaim® 120 C18 and the Acclaim® RSLC C18 PA2 to separate tryptic digested proteins from cell lysate. The researchers found that the Acclaim® RSLC C18 PA2 had higher efficiencies and exhibited higher polarity of selectivity.…”
Section: Hplc Columnsupporting
confidence: 69%
“…Based on prior tetracycline antibiotic research, we hypothesized that sample preparation techniques, namely an additional filtration step to remove remaining particulates that can interfere with HPLC performance (CDER, 1994), and HLPC characteristics, such as mobile phase solution (Jia, Xiao, Hu, Asami, & Kunikane, 2009), column type (Ritorto et al, 2014) and wavelength (Ng, & Linder, 2003), would influence antibiotic detection in water samples. We anticipated that analysis of larger sample volumes would improve antibiotic detection, as we would have a more material from which to develop a concentrate, while higher manure concentrations would decrease detection capabilities due to the presence of more impurities requiring removal to not inhibit HPLC performance.…”
Section: Secondary Sample Preparationmentioning
confidence: 99%
“…Usp8 shows some selectivity for recombinant K63-ubiquitin linkages in vitro (28,29). However, compared with other DUBs of the cysteine protease type, Usp8 as well the closely related enzyme Usp7 showed strong capacity to hydrolyze K63-linked ubiquitin on α-synuclein in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…We tested this in HepG2 cells, and despite obtaining effective silencing of USP7, both expression of IDOL and the response to DUB inhibition remained unaffected (data not shown). A potential explanation for this result is recent evidence indicating that HBX41-108 has a much broader substrate specificity and is able to inhibit a large panel of cysteine DUBs, similar to PR-619 (35,36). The fact that multiple DUBs are sensitive to these inhibitors has precluded us from identifying a specific DUB responsible for the induction of IDOL.…”
Section: Lxr␣␤mentioning
confidence: 86%